Landscape complexity differentially affects alpha, beta, and gamma diversities of plants occurring in fencerows and crop fields - Poggio, Santiago Luis (2010)
Agro-ecosystems still retain part of the original biodiversity, although agricultural intensification threatens to eliminate refuge patches from farmland mosaics. Landscape complexity resulting from networks of uncultivated corridors associated with fencerows may play a key role in sustaining biodiversity across scales, and may further influence diversity in adjacent, cultivated fields. We evaluated the relationship between farmland complexity and plant diversity of fencerows and crop fields at local and landscape scales in the Rolling Pampas of Argentina. We surveyed 222 fencerows and fields cultivated with winter or summer crops, and characterised farmland complexity by the perimeter/area ratio of cropland in 2-km diameter circles surrounding each field. Plant diversity was additively partitioned into alpha, beta, and gamma components. Fencerows had noticeably higher richness than cropped fields at local and landscape scales. Gamma and beta diversities of fencerows and fields were positively related to farmland complexity, supporting the role of spatial heterogeneity in maintaining plant diversity in agro-ecosystems. Landscape complexity did not influence alpha diversity of fencerows but significantly increased diversity within fields, a likely result of enhanced mass effects from uncultivated habitats in more varied farmland. More complex landscapes contained greater gamma diversity of exotic perennials in fencerows, and of exotic and native annuals within fields. Importantly, alpha and gamma diversities of native perennials from the pristine Pampa grassland increased with landscape complexity within cropped fields. In the face of ongoing landscape homogenisation under agricultural intensification, maintaining fencerow networks may become critical for conserving habitat heterogeneity and farmland biodiversity. © 2010 Elsevier Ltd.